iPSC-Derived Endothelial Cells Affect Vascular Function in a Tissue-Engineered Blood Vessel Model of Hutchinson-Gilford Progeria Syndrome - Leigh Atchison (Stem Cell Reports, 2020)
Summary: Hutchinson-Gilford progeria syndrome (HGPS) is a rare disorder caused by a point mutation in the Lamin A gene that produces the protein progerin. Progerin toxicity leads to accelerated aging and death from cardiovascular disease. To elucidate the effects of progerin on endothelial cells, we prepared tissue-engineered blood vessels (viTEBVs) using induced pluripotent stem cell-derived smooth muscle cells (viSMCs) and endothelial cells (viECs) from HGPS patients. HGPS viECs aligned with flow but exhibited reduced flow-responsive gene expression and altered NOS3 levels. Relative to viTEBVs with healthy cells, HGPS viTEBVs showed reduced function and exhibited markers of cardiovascular disease associated with endothelium. HGPS viTEBVs exhibited a reduction in both vasoconstriction and vasodilation. Preparing viTEBVs with HGPS viECs and healthy viSMCs only reduced vasodilation. Furthermore, HGPS viECs produced VCAM1 and E-selectin protein in TEBVs with healthy or HGPS viSMCs. In summary, the viTEBV model has identified a role of the endothelium in HGPS. : Atchison and colleagues produced hiPSC-derived vascular smooth muscle cells and vascular endothelial cells from healthy and progeria patients. These cells were used to fabricate functional tissue-engineered blood vessels that express key features of the progeria cardiovascular phenotype. This work provides a novel platform to study progeria and other cardiovascular diseases using iPSC-derived cells in an in vitro platform. Keywords: Hutchinson-Gilford progeria syndrome, tissue-engineered blood vessel, microphysiological system, induced pluripotent stem cells, vascular endothelium, smooth muscle cells, shear stress